2014
DOI: 10.1186/1297-9716-45-44
|View full text |Cite
|
Sign up to set email alerts
|

Memory T cell proliferative responses and IFN-γ productivity sustain long-lasting efficacy of a Cap-based PCV2 vaccine upon PCV2 natural infection and associated disease

Abstract: Porcine circovirus type 2 (PCV2) vaccination represents an important measure to cope with PCV2 infection; however, data regarding the modulation of the immune cell compartment are still limited, especially under field conditions. This study is aimed at investigating the features of the cellular immune response in conventional piglets induced by vaccination using a capsid (Cap) protein-based PCV2 vaccine compared to unvaccinated animals when exposed to PCV2 natural infection. Immune reactivity was evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 46 publications
7
16
0
Order By: Relevance
“…Conversely, the increased numbers of IFN-γ SCs as well as the reduced CV in the blood at T3 and T4 could be influenced by an undetected infection with PCV-2 during gestation. As demonstrated in previous studies (Martelli and others 2011, 2013, Ferrari and others 2014) in vaccinated animals, soon before the onset of infection the recalled PCV-2-specific immune response is characterised by moderate PCV-2-specific IFN-γ SC frequencies and augmented productivity together with reactive CD4+CD8+ cells (memory T cells). So, after vaccination the number of IFN-γ SCs usually has an increase within two weeks, but, subsequently, it can run with an erratic trend in the blood, frequently at a lower level than the primary activation.…”
supporting
confidence: 66%
“…Conversely, the increased numbers of IFN-γ SCs as well as the reduced CV in the blood at T3 and T4 could be influenced by an undetected infection with PCV-2 during gestation. As demonstrated in previous studies (Martelli and others 2011, 2013, Ferrari and others 2014) in vaccinated animals, soon before the onset of infection the recalled PCV-2-specific immune response is characterised by moderate PCV-2-specific IFN-γ SC frequencies and augmented productivity together with reactive CD4+CD8+ cells (memory T cells). So, after vaccination the number of IFN-γ SCs usually has an increase within two weeks, but, subsequently, it can run with an erratic trend in the blood, frequently at a lower level than the primary activation.…”
supporting
confidence: 66%
“…where significantly higher levels of IFN-γ-SCs were observed in piglets from vaccinated sows with regard to the ones from unvaccinated sows after colostrum ingestion. The assessment of IFN-γ-SCs is commonly used to measure the cell-mediated immunity response, mainly for the following reasons: 1) the levels of PCV2 specific IFN-γ-SCs increase after infection and vaccination (Fort et al, 2009;Koinig et al, 2015); in fact, PCV2 vaccination induces a long-lasting immunity sustained by memory T cells and IFNγ secreting cells that might participate in the prevention of PCV2 infection (Ferrari et al, 2014); 2) IFN-γ-SCs are inversely correlated with PCV2 viral loads in serum (Seo et al, 2012a;Seo et al, 2012b); and 3) these T cells are specific for both PCV2 Cap and Rep proteins (Fort et al, 2010). However, to the authors' knowledge, information about general cytokine profiles in piglets after colostrum ingestion is missing in the peerreviewed literature.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, B and CD3 + CD4 + CD8+ memory/activated Th lymphocytes are depleted and this depletion is related to the development of PCV2-SD [45]. Both vaccination and infection elicit memory/activated Th cells [44, 46]. These cells are activated, antigen specific T cells and memory cells.…”
Section: Introductionmentioning
confidence: 99%
“…These cells are activated, antigen specific T cells and memory cells. Antigen specific memory T cells persist long term post-infection/vaccination and are able to expand rapidly after recall antigen recognition, thus being able to prevent PCV2 infection quickly [46]. More specifically, it has been suggested that PCV2 specific IFN-γ/TNF-α co-producing CD4 + cells, which are produced upon vaccination/infection, play a central role in controlling and clearing PCV2 infection [44].…”
Section: Introductionmentioning
confidence: 99%